Pelatihan Pengolahan Minyak Goreng Bekas Industri Kerupuk Kulit Menjadi Sabun Padat di Kelurahan Kamang Magek - Ulia, Hasnah; Rahayu, Puji; Rahmad, Dedy; Rosalina, Rosalina; Putri, Dwi Kemala; Nurrahmi, Rara (Journal of Industrial Community Empowerment, 2022)
Most of the residents of Kamang Magek work as entrepreneurs. The type of business that is developing a lot is the production of skin crackers or known as "Karupuak Jangek" on a household scale. These crackers are made from cow or buffalo skin, which produces approximately 300 kg of crackers per household center. From these productions, a lot of used cooking oil is produced by ± 1000 L per week. One way to improve the quality of the cooking oil waste is to process it into an innovation, one of which is solid soap. Solid soap is made from neutral fats from oils that have been hardened, by a hydrogenation process, using alkaline NaOH. What's more, during the current pandemic, solid soap is needed a lot to reduce the potential for COVID-19 transmission. Currently, the community already has the expertise to process used cooking oil to be used as the basic material for making solids. These skills can become a new hobby for some people who are able to increase the selling value of waste.